The state of antioxidant protection system in cows under the influence of heavy metals - L. G. Slivinska; A. R. Shcherbatyy; B. O. Lukashchuk; B. V. Gutyj (Regulatory Mechanisms in Biosystems, 2020)
A highly relevant problem of modern veterinary science is the study of features and mechanisms of combined action of the most common heavy metals – cadmium and plumbum and their influence on the body of humans and animals in the regions of Ukraine under technogenic pollution. The purpose of the work was to study the influence of heavy metals on the state of the antioxidant protection system of cows, in particular on the content of lipid peroxidation products (malonic dialdehyde, lipid hydroperoxides and diene conjugates), and activity of antioxidant enzymes (glutathione peroxidase and superoxide dismutase), depending on the distance to the heaps of mines in the coal basin. The study objects were cows of black-and-white breed at the age of 3–7 years. It was established that this parameter in the place with the highest concentration of diene conjugates in the blood of cows was by 25.8 % higher compared to the place of low concentration and 12.1 % higher compared to the place with medium concentration. In the place with the highest content of lipid hydroperoxides in the blood of cows the parameter was 23.7 % higher compared to the cows from the place with the low content. The concentration of lipid hydroperoxides in the blood of cows from the place with the medium content was 16.7% higher compared to the cows from the place with the low content. The parameter from the place with the lowest content of lipid hydroperoxides in the blood of cows was 12.1% lower compared to the place with the highest content. The level of malonic dialdehyde in the blood of cows from the technogenic pollution zone in the place with the largest amount was higher by 36.2; 34.0 and 18.8 % – compared to places with medium and low levels, respectively. The activity of superoxide dismutase in the blood of cows in the place with its highest activity was 0.284 ± 0.0099 % block. reac/g Hb, and in the place with the lowest activity – 0.23 ± 0.0051 % block. reac/g Hb. The activity of glutathione peroxidase in the blood of cows in farms of the technogenic pollution zone depended on the distance to the mine. These researches will further develop effective methods of treating cows under the influence of heavy metals, in particular regarding the antioxidant system.